Extended School Year (ESY) - Pinkerton, Dianna; Council for Exceptional Children, Reston, VA.; ERIC Clearinghouse on Handicapped and Gifted Children ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This digest defines the term "extended school year" (ESY) and notes the issues of regression and recoupment which have led to development of ESY services for students with disabilities. The digest then provides answers to the following questions: (1) When is ESY needed? (2) How is eligibility for ESY determined? (3) What are some factors that could mandate a need for ESY? (4) What other factors may be considered in offering an ESY program? and (5) What types of delivery models are available? Includes 13 references. (JDD)
Availability: Council for Exceptional Children, Publication Sales, 1920 Association Dr., Reston, VA 22091-1589 ($1.00 each, minimum order $5.00 prepaid).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: RI88062007.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Delivery Systems; Disabilities; Educational Practices; Elementary Secondary Education; Eligibility; Extended School Year; Models; Student Needs; ERIC Digests; ERIC Publications; Guides, Non-Classroom.; ERIC Digests in Full Text